Lessons from the controversy over statins - Authors' reply. - Armitage, J; Baigent, C; Collins, R (Elsevier, 2016)
Virginia Barbour states in her letter that, with respect to the submission to the Committee on Publication Ethics (COPE) in October, 2014, by a group of senior doctors and scientists, she had “recused myself because of a potential conflict of interest”. However, that is not strictly accurate; Barbour only recused herself in September, 2015, 8 months after she had adjudicated on the submission in January, 2015.